Development of Guided Inquiry Learning Tools Assisted by PhET Simulation to Improve Student’s Learning Motivation in the Sub Material of Molecular Shapes - Eryna Dwi Trisviati; Achmad Lutfi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This research is purposed to obtain a PhET-assisted guided inquiry learning tools that is feasible to use in improving student learning outcomes and motivation in terms of validity, practicality, and effectiveness. A limited trial was held in SMA Khemala Bhayangkari 1 Surabaya. The instruments used were validation sheets, student response questionnaire sheets, student motivation questionnaire sheets, pretest and posttest. The development model used is 4D which is simplified into define, design, and develop. The learning tools was declared valid with a score of 3 as the minimum score to be included in the category of good. The practicality of learning tools is stated to be practical built upon the outcomes of response questionnaires done by students with a percentage of more 92.3% as greatly practical criteria. Learning tools is said to be effective based on the results of the student motivation questionnaire with a percentage of 84.6% as criteria of very high and learning outcomes gaining an N-Gain value in the category of high. So, it can be concluded that the guided inquiry learning tools  assisted by PhET Simulation fulfills the effectiveness, practicality, and validity. The researcher hopes who want to develop learning tools to take advantage of  these tools.